Effective student feedback as a marker for student success - Cohen, A.; Singh, D. (South African Journal of Higher Education, 2020)
Enhancing the learning journey of a student requires feedback that is thoughtful, relevant and in-depth. Nicol (2010) as cited by UNSW Sydney (2018) stated that “feedback is valuable when it is received, understood and acted on. How students analyse, discuss and act on feedback is as important as the quality of the feedback itself”. This sentiment is echoed by Hattie (1999), also cited by UNSW Sydney (2018), when he stated that “feedback is the most powerful single moderator that enhances achievement”. Feedback is one of the most important activities undertaken by educators in the realm of higher education. A student learning journey devoid of reliable, clear, consistent, and efficient feedback is a journey that is devoid of growth, cognitive development, intellectual challenge, and possibly even success. The theoretical value and benefits of feedback in the teaching and learning process is well-documented. Therefore, it is an epistemological conundrum when further evidence indicates that students’ attitudes to feedback is either indifferent or totally negative. The feedback process is one of symbiosis between the educator and the student, with no one element of this relationship being more important than the other. The manner in which feedback is provided by the educator and the manner of engagement by the student determines the success of the process. A survey at a private higher education institution investigates the quality of feedback provided by educators and the extent to which the students on the receiving end engage with and act on the feedback received.